2011
DOI: 10.1166/jbn.2011.1291
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Ammonium Functionalized Porous Poly(glycidyl methacrylate-co-ethylene dimethacrylate) Monoliths for Microscale Analysis and Its Application to DNA Purification

Abstract: International audienceA systematic study of parameters affecting the nucleophilic addition of secondary and tertiary amines on reactive epoxy groups was conducted on porous polymer monoliths. Reaction of small amines like diethylamine (DEA) or triethylamine (TEA) on poly(glycidyl methacrylate-co-ethylene dimethacrylate) monoliths (poly(GMA-co-EDMA)) allows to prepare anion exchange media. This study aimed to determine optimal and suitable conditions to prepare anion-exchange porous monolith inside 100 tun inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Here, we showed that the transfer of well‐established thermally induced polymerization to photo‐induced polymerization can be a relevant way to enhance the IEC of glycidyl‐based monolith. Using the efficient mixture defined by Ueki et al 11 and our previously published functionalization procedure 44, the present study demonstrates the potential of this strategy to obtain monoliths with unmatched chromatographic performances.…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…Here, we showed that the transfer of well‐established thermally induced polymerization to photo‐induced polymerization can be a relevant way to enhance the IEC of glycidyl‐based monolith. Using the efficient mixture defined by Ueki et al 11 and our previously published functionalization procedure 44, the present study demonstrates the potential of this strategy to obtain monoliths with unmatched chromatographic performances.…”
Section: Introductionmentioning
confidence: 54%
“…30 min irradiation) in 100 μm id Teflon‐coated capillaries. Single‐step preparation of quaternary ammonium functionalized monolith has been carried out according to a previously published procedure 44. Briefly, monolithic capillary columns were filled with a solution of TEA in 50:50 v/v EtOH/water.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The more convenient way to insert solid stationary phases inside microchannels relies on the in situ synthesis of porous materials such as organic or inorganic monoliths. Photopolymerized organic monoliths can be in situ synthesized using a large variety of monomers (mainly acrylate and methacrylate ones) that allow covering a wide range of interaction mechanisms from ion exchange to popular RP mode . However, each modification in the polymerization mixture implies a time‐consuming reoptimization of the entire polymerization process.…”
Section: Introductionmentioning
confidence: 99%
“…The more convenient way to insert solid stationary phases inside microchannels relies on the in situ synthesis of porous materials such as organic or inorganic monoliths. Photopolymerized organic monoliths can be in situ synthesized [8][9][10][11][12][13] using a large variety of monomers (mainly acrylate and methacrylate ones) that allow covering a wide range of interaction mechanisms from ion exchange to popular RP mode [14]. However, each modification in the polymerization mixture implies a timeconsuming reoptimization of the entire polymerization pro-Correspondence: Dr. Racha El Debs, Université Claude Bernard Lyon1, 5 rue de la doua, Villeurbanne 69100, France E-mail: racha.debs@hotmail.com Fax: +33(0)472448319 Abbreviations: AIBN, 2,2 -azobisisobutyronitrile; BME, benzoin methyl ether; ␥-MAPS, [␥-(methacryloyloxy)propyl]trimethoxysilane; META, [2-(methacryloyloxy) ethyl]trimethylammonium chloride; ODS, octadecyldimethylchlorosilane; TEA, triethylamine cess.…”
Section: Introductionmentioning
confidence: 99%